Crisis communication in the civil protection system in emergency situations - Sočković, Ivica; Budimir, Blaženka; Bida, Igor (Crisis Management Days, 2024)
Abstract: It is common knowledge that marketing techniques and principles work well in organizations operating in an open market where competition is high. However, in the public sector, where there is no competition, the principles and techniques of marketing are either not applied at all or are applied to a much smaller extent compared to organizations operating in a competitive market. As digital technologies are increasingly applied, new business opportunities are offered, new information media are offered, information is becoming more and more available, and the demands of citizens for improvements in public sector services are also increasing. In the past years in the territory of the Republic of Croatia, we had significant emergency situations such as floods, earthquakes, fires, infectious diseases. In these and similar situations, a large proportion of calls to the number 112 are of the same or similar nature, when citizens are mostly looking for some information related to a specific event or phenomenon. 112 centers occupy a central place in the civil protection system, which is evident in emergency situations when numerous information from the field pour into the unique European number for emergency services 112 in real time. In crisis situations, quick and accurate information or instructions to citizens come to the fore in the civil protection system, which is delivered to a large number of interested citizens in the form of a press release for the population via electronic media. At the same time, the announcement for the population relieves the 112 centers of a large number of the same or similar calls from citizens.The paper aims to show the possibilities for faster, more successful and more efficient public sector communication in crisis situations if marketing techniques and principles that are proven to work in the real sector are applied. 1. INTRODUCTION Technical-technological and human capacities for receiving calls to the number 112 are limited, and in order to reduce the number of calls to the number 112 in crisis situations, it is necessary to inform the public as efficiently as possible and give instructions on how to act in emergency situations. In order to inform as many citizens as possible about the purpose of the existence of a single European number for emergency services 112, and in emergency situations in as short a time as possible to inform as many citizens as possible about the extraordinary event that has occurred, the efficiency and effectiveness of marketing communication of the public sector is being researched.The quality of life of millions of people in modern countries depends on the knowledge, skills, efficiency, effectiveness, loyalty and morals on the basis of which the public sector performs its duties and achieves the goals entrusted to it in the realization of public interests and the promotion of the common good. The public sector is a common name for the sector of the general government and public enterprises owned by the state. The public sector includes all institutions owned by the state that produce public goods and services. The basic task of the public sector is to ensure that the needs and interests of citizens are met.When we talk about the public sector, we have to say that marketing is one of the most neglected and least researched areas by public sector officials. Marketing in the public sector is the best tool for planning in a public organization that wants to meet the needs of citizens and deliver real value.In the public sector, already proven marketing principles and techniques should be applied in order to achieve goals that contribute to the common good. One of the ways to improve the work of public services is the active implementation of various mechanisms and techniques that the private sector has tried, used and proven to be successful. Traditional marketing terms work well in the public sector as well; they just need to be applied. 1.1. Research subject The paper investigates and analyzes the marketing activity of the civil protection system, especially communication on websites and social networks, as well as other electronic media through which announcements are made to the population in crisis situations. 1.2. Research hypotheses H1 – The civil protection system does not fully use all the potential and benefits of electronic media, especially the Internet and social networks for communicating with the public, and the communication in question can be more effective if marketing principles that have been proven to work well in the real sector are properly applied.H2 – The potential for greater efficiency in the communication of the civil protection system with the interested public and better connection with users of social networks exists in the hitherto unused possibilities of each regional office of civil protection in the counties having its own accounts - pages on social networks.H3 – When providing information to the population, the civil protection system, in addition to Croatian Radio and Croatian Television, must necessarily use other electronic media that have concessions at the state level. 1.3. Purpose and objectives of the research The purpose and objectives of the research of this work are to investigate and formulate the results of the research in connection with the marketing communication of the civil protection system. The special goal of the research is to get answers to the following questions:Can the effectiveness of the marketing communication of the civil protection system be increased?Does the civil protection system use all the potential offered by information and communication technologies, especially social networks, for communication with the public at the local levels where regional civil protection offices operate?Does the civil protection system use all the potential of available electronic media to communicate to the population? 1.4. Research methods Primary and secondary sources were used to create this final paper. Available literature in the form of books and other publications and internet sources related to marketing, marketing communication, social networks, crisis and crisis situations were used as secondary sources. The results of our own research were used as primary sources.When researching, formulating and presenting research results, the following scientific methods were used in combinations: the method of analysis and synthesis, the method of induction and deduction, the historical method, the method of classification, the method of description and the method of compilation, and the method of surveying.Two surveys were conducted, one survey was conducted among the population aged 20 to 65 (working population), while the second survey was conducted among school children from preschool age to high school graduates and among retirees.The results of the primary research are compared with the results from secondary sources as well as with the theoretical part of the research, and a conclusion is drawn based on this.